Understanding high fructose corn syrup in popular snacks: Consumption, perceptions and labeling preferences - Oscar Sarasty; Modhurima Dey Amin (PLoS ONE, 2026)
At a time when the Make America Healthy Again (MAHA) initiative brought renewed attention to High Fructose Corn Syrup (HFCS), this study explores the potential of supplemental labeling to inform consumers. Consumption of sugary items, including those containing HFCS, has been linked to non-communicable diseases like obesity in literature. We conduct a survey to examine respondents’ perceptions and valuations of HFCS and their support for supplemental information labeling programs indicating the presence of HFCS, and the willingness to pay for HFCS labels in three food products. We find that 93% of consumers know what HFCS is, while over 58% report that all or most of the products they consume contain HFCS. Results from choice experiments suggest that consumers are willing to pay positive price premiums up to 16% of the average price for products with labels indicating the absence of HFCS. The findings suggest that supplemental HFCS labeling could serve as both a public health tool and a managerial policy lever—helping consumers make more informed choices while supporting broader efforts to reduce non-communicable diseases associated with excessive HFCS consumption. Additionally, the results provide food manufacturers with a strategic opportunity to align with evolving consumer preferences and potentially capture price premiums for HFCS-free products.